A scoping review of life skills development and transfer in emerging adults - Tanious, René; Gérain, Pierre; Jacquet, Wolfgang; Van Hoof, Elke (Frontiers in Psychology, 2023)
Emerging adulthood is a unique and sensitive life period during which most psychiatric conditions emerge. Development of life skills and transfer of these skills between contexts may be considered essential for transitioning from emerging adulthood to young adulthood. In the present scoping review of 83 articles published between 2010 and 2022, we address the state of research on life skills development and transfer in emerging adults aged 18–30. Specifically, we were interested in how life skills are defined, which specific life skills are proposed and how life skills transfer is conceptualized for this age group, with an emphasis on cognitive, personal, and interpersonal components. The results show that only a small minority of the reviewed studies defined the term life skills and an even smaller number mentioned the concept of life skills transfer, with only one study actually mentioning transfer components. Life skills research for emerging adults strongly focuses on vulnerable populations (e.g., developmental and contextual vulnerabilities, and sexually transmittable infections treatment and prevention) with the five most frequently mentioned life skills being budgeting/ finances, communication, problem-solving, decision-making, and emotional regulation. We discuss these results in light of future research directions and the lessons learned for life skills development and transfer research in emerging adults. Systematic review registration All analyzed articles are available at: https://osf.io/gmk8w/.